Report on prioritization of food safety issues in the dairy and horticulture value chains, Kenya - Kang'ethe, Erastus K.; Muriuki, Samuel; Karugia, Joseph T.; Guthiga, Paul M.; Kirui, Leonard (International Livestock Research Institute, 2019)
Food borne diseases can be caused by biological, chemical and physical hazards. Most food borne illnesses result from consumption of animal source foods and fruits and vegetables. Managing food borne illness requires establishment of food safety control systems. In resource poor countries, it imperative that prioritization of the causes of food borne illness be done to have better resource allocation and utilization. A team of experts drawn from dairy and horticulture value chains listed the key food safety hazards in the dairy and horticulture value chains. A multi-criteria approach was used to prioritize the food safety hazards and associated aspects of food loss and trade. Microbial hazards were ranked highly in both value chains. This is a reflection of poor agricultural and post-harvest handling practices of the commodities. Considering the dominance of smallholder production in the two value chains, observance of good agricultural and hygienic practices is challenging along value chains that have many nodes and actors. The situation can be addressed through capacity building and adoption of good agricultural and hygienic practices, enforcement of food safety standards and provision of appropriate infrastructure development along the value chains.